Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds

Novel synthesis of nano-calcium carbonate (CaCO3)/polystyrene (PS) core-shell nanoparticles by atomized microemulsion technique and its effect on properties of polypropylene (PP) composites - Mishra, Satyendra; Chatterjee, Aniruddha; Singh, RajPal (Polymers for Advanced Technologies, 2011)
Calcium carbonate (CaCO3)/polystyrene (PS) nanoparticles (< 100 nm) with core-shell structure were synthesized by atomized microemulsion technique. The polymer chains were anchored onto the surface of nano-CaCO3 through triethoxyvinyl silane (TEVS) as a coupling agent. Ammonium persulfate (APS), sodium dodecyl sulfate (SDS) and n-pentanol were used as initiator, surfactant, and cosurfactant, respectively. Polymerization mechanism of core-shell latex particles was discussed. Encapsulation of nano-CaCO3 by PS was confirmed by using transmission electron microscope (TEM). Grafting percentage of core-shell particles was investigated by Thermogravimetric Analyzer (TGA). Nano-CaCO3/PS core-shell particles were characterized by Fourier transform infrared (FTIR) spectrophotometer and differential scanning calorimeter (DSC). The results of FTIR revealed existence of a strong interaction at the interface of nano-CaCO3 particle and PS, which implies that the polymer chains were successfully grafted onto the surface of nano-CaCO3 particle through the link of the coupling agent. In addition, TGA and DSC results indicated an enhancement of thermal stability of core-shell materials compared with the pure nano-PS. Nano-CaCO3/PS particles were blended with polypropylene (PP) matrix on Brabender Plastograph by melt process with different wt% of loading (i.e. 0.1-1 wt%). The interfacial adhesion between nano-CaCO3 particles and PP matrix was significantly improved when the nano-CaCO3 particles were grafted with PS, which led to increased thermal, rheological, and mechanical properties of (nano-CaCO3/PS)/PP composites. Scanning electron microscope (SEM) and atomic force microscope (AFM) images showed a perfect dispersion of the nano-CaCO3 particles in PP matrix. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: atomized microemulsion; core-shell nanoparticles; mechanical properties; polypropylene (PP); Rheological properties; Thermal properties